A comparison of emergency airway management between neuromuscular blockades alone and rapid sequence intubation: an analysis of multicenter prospective study. (December 2017) - Sato, Nobuhiro; Hagiwara, Yusuke; Watase, Hiroko; Hasegawa, Kohei
Abstract Background Although airway management with neuromuscular blockade (NMB) alone is discouraged in the emergency department (ED), our previous study demonstrated that many patients were intubated using NMBs alone without sedatives. To refute this practice, we sought to compare the intubation success and adverse event rates between NMBs only and rapid sequence intubation (RSI). Methods This is a secondary analysis of the data from a prospective observational study of ED patients in 13 hospitals who underwent emergency airway management from April 2010 to August 2012. The primary outcome was intubation success rate on first attempt. The secondary outcomes were the intubation success rate in ≤2 attempts and the intubation-related adverse event rate. We compared these outcomes between intubation attempts using NMB alone and RSI. We fit multivariable logistic regression models adjusting for potential confounders (age, sex, weight, primary indication for intubation, and training level of intubators). Results Overall, 852 patients were eligible for this analysis, with 114 (13%) intubated with NMB alone and 738 (87%) with RSI. Between the NMB-alone and RSI groups, no significant differences were observed in the success rate on the first attempt (70 vs. 73%; P = 0.48) or in ≤2 attempts (89 vs. 91%; P = 0.46), or in the adverse event rate (11 vs. 12%; P = 0.58). Similarly, after adjusting for confounders, no significant differences were observed in any of these outcomes (all P > 0.05). Conclusions In this analysis of data from a large multicenter study of ED patients, we found no superior effectiveness of intubation with NMB alone when compared to RSI. Our data lend significant support to the concept that intubation with NMB alone should be avoided in the ED.